2014
DOI: 10.1177/0003489414525924
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Air Escape via the Nasolacrimal System

Abstract: CRANS represents a previously undescribed clinical entity. CRANS may be responsible for some CPAP-related eye side effects and possibly for rarer secondary eye complications, including conjunctivitis and corneal ulceration. CRANS should be suspected in any patient on CPAP complaining of eye symptoms. CRANS may be diagnosed through careful observation during A-PSG and confirmed by performing a "saline bubble test." Management options include nonsurgical (mask alternatives, humidification, nasopharyngeal airway)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Irritation and contact lens dryness were found in patients using chemical protection hoods that blow air across the inside of the face mask [4]. Continuous positive airway pressure (CPAP) masks may cause ocular surface irritation due to air leakage or regurgitation through the nasolacrimal system [5,6]. All of these studies suggest that increased air convection affects the eye; however, this process is not described in the context of face mask use.…”
mentioning
confidence: 99%
“…Irritation and contact lens dryness were found in patients using chemical protection hoods that blow air across the inside of the face mask [4]. Continuous positive airway pressure (CPAP) masks may cause ocular surface irritation due to air leakage or regurgitation through the nasolacrimal system [5,6]. All of these studies suggest that increased air convection affects the eye; however, this process is not described in the context of face mask use.…”
mentioning
confidence: 99%
“…Interestingly, even in the absence of detectable mask leaks, CPAP-associated retrograde air flow via the nasolacrimal system (CRANS) may be evident by a saline bubble test during CPAP use 34 , a mechanism previously suggested to have implications in dry eye and conjunctivitis. 31 , 35 …”
Section: Discussionmentioning
confidence: 99%
“…In this study, all 6 unoperated nasolacrimal systems showed no AR at the highest testable level (30 cm H2O), consistent with the rare occurrence of AR in CPAP patients with unoperated nasolacrimal systems. 5, 6…”
Section: Discussionmentioning
confidence: 99%
“…While air regurgitation through an unoperated nasolacrimal system in patients using CPAP occurs only rarely, it may occur after DCR in about 70% of cases. 58 Regurgitation is associated with greater patency and higher success rate of DCR surgery. 4, 9, 10 Associated symptoms, including difficulty sleeping, dry eyes, eye pain, and blurry vision, significantly disrupt CPAP compliance in up to 43-50% of patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation